A Retrospective Study on English Teachers' Strategies to Improve Students' Speaking Fluency - Bunga Yolandita Siahaan; Cindi Rajagukguk; Erikson Saragih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
A retrospective study on English teachers' strategies to improve student fluency describes strategies implemented by teachers to enhance student fluency. It is also the most effective strategy for improving the speaking ability of students. Whereas there are many studies on teachers' speaking skills in Indonesia, there are still few studies argue teachers' speaking strategies to improve students' speaking skills. The purpose of this study is to find strategies that teachers can apply to enhance their students' fluency in English and effective strategies that can be used in learning to improve their students' fluency. This research method uses the qualitative research method and survey design. As a research tool, researcher used a questionnaire that was distributed to 10 English teachers who were used as respondents or research subjects by the researchers. The researchers then collected responses from the questionnaire, and from the results of the data collected, the researchers found that the strategies used by teachers had a significant impact on improving students' fluency. The methods used by teachers should be effective and understandable to students. Similar to, use of media to support achievement of learning indicators. Furthermore, teachers must be able to invite students to take an active role in learning by motivating them. Based on this research, we can conclude that speaking is one of the basic skills that language learners must master. Strategies employed by teachers have a significant impact on student fluency development.